Pengaruh Service Failure dan Service Recovery Terhadap Loyalitas Pelanggan Indomaret: (Studi Kasus pada Pelanggan Indomaret di Kelurahan Pademangan Barat, Kecamatan Pademangan, Kota Jakarta Utara) - Sonista, Muhamad; Jati Saputro, Restu; Hadikusuma, Riza (Jurnal Administrasi Profesional, 2024)
This study aims to evaluate how service failure and service recovery affect customer loyalty at Indomaret located in Pademangan Barat Village, Pademangan District, North Jakarta. Data were collected through questionnaires using non-probability sampling techniques, specifically purposive sampling method, with a total sample of 100 respondents. The data were analyzed using statistical software Smart Partial Least Square version 4.1.0.3 (SmartPLS 4.1.0.3). The results showed that service failure has a significant negative effect on customer loyalty with a coefficient of -0.203 and p-values of 0.016, while service recovery has a significant positive effect with a coefficient of 0.512 and p-values of 0.000. In addition, the combination of service failure and service recovery can explain 29.1% of the variation in customer loyalty, as shown by the R-squared value of 0.291.